Biological Active Ingredients of Traditional Chinese Herb Astragalus membranaceus on Treatment of Diabetes: A Systematic Review - Kai, Zhang; Michela, Pugliese; Antonio, Pugliese; Annamaria, Passantino (Mini Reviews in Medicinal Chemistry, 2015)
Diabetes mellitus (DM) is a serious chronic metabolic disease which disease afflicting at present now afflicts approximately 4% of world population worldwide. Nowadays, the need for more potent and safe drugs to supply the present anti-diabetic and treated drugs has become an imperative. Astragalus membranaceus, the most common Chinese herb and key-component of many Chinese herbal anti-diabetic formulas, is rich in anti-diabetic compounds: polysaccharides (APS), saponins (ASS), and flavonoids (ASF) etc. Because of its various biological activities, especially its antidiabetic properties, that continuously arouse different studies. Recent studies focused on type 1 and type 2 treatment, respectively caused by autoimmune destruction of pancreatic beta cells and insulin resistance and deficient glucose metabolism. Its total polysaccharides, saponins and flavonoids fractions and several isolated compounds have been the most studied. This paper discusses diabetic treatment and pharmacological action of the biological ingredients in relation to diabetes mellitus and diabetic complications.
Keywords: Astragalus flavonoids